LANGAUGE ANXIETY IN SPEAKING ENGLISH: A DESCRIPTIVE STUDY ON SECOND GRADERS OF SENIOR HIGH SCHOOL - Siska Teriska, - (2011)
This paper is entitled "Language Anxiety in Speaking English: A Descriptive Study on Second Graders of Senior High School". The purpose of this study is to present the view of language anxiety of senior high school students' in speaking English, find out the levels of anxiety perceived by senior high school students, identify the sources and the situation that may trigger or causes anxiety, and to present strategies which may be helpful for senior high school students to cope with the language anxiety. A descriptive method is used in obtaining the data of this study. An adapted questionnaire of Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz, Horwitz, and Cope (1991) is administered to 40 students of an english class in a Senior High School Bandung . Besides, an open ended questionnaire and a classroom observation were used to add the data about the sources and the situation that may trigger or causes of anxiety and the strategies used by the students. The results showed that most of the students were 'mildly anxious' (45%) in speaking English. Besides, there were four 'very anxious' students (10%), nine 'anxious'students (22.5%), eight 'relaxed' students (20%), and just one 'very relaxed' student (2.5%). The causes of anxiety came from themselves, such as their low proficiency and their confidence, and came from particular situation or their surrounding, such as their teacher and classmates behavior. The strategies used by them was then categorized as the strategies mentioned by Kondo and Yang (2004) : 'preparation', 'relaxation', 'positive thinking', 'peer seeking', and 'resignation'. Findings show that most of them used 'relaxation strategies'. It is understandable since it reduced their tension when having the lesson.